Analisis Efektivitas Dan Efisiensi Anggaran Unit Reskrim Polsek Marga Tiga Polres Lampung Timur - Anjelina, Kadek; Hendri, Nedi; Febri Darmayanti, Elmira (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to determine how the budget realization of the effectiveness and efficiency of the performance of the Marga Tiga Police Criminal Investigation Unit of the East Lampung Police in the 2019-2023 budget year through budget realization and analyzing inhibiting factors in realizing the budget analyzed using quantitative descriptive methods. The population in this study was the Marga Tiga Police, East Lampung Police, while the research sample was the budget distribution report (resdisgar) and financial accountability report (perwabkeu) of the Marga Tiga Police Criminal Investigation Unit for the 2019-2023 budget year. The results of this study indicate that the level of budget effectiveness at the Marga Tiga Police Criminal Investigation Unit for the 2019-2023 budget year is entirely said to be ineffective. The development of the level of budget management efficiency at the Marga Tiga Police Criminal Investigation Unit for the 2019-2023 Budget Year can be said to be very efficient in managing the budget. Factors that can hinder the realization of the budget in the Marga Tiga Police Criminal Investigation Unit are individual factors and environmental factors.